Tata Motors’ acquisition of Jaguar Land Rover - Mukherjee, Deepraj (Henry Stewart Talks, 2016)
Emerging country multinationals, FDI behavior diagram, Case description in chronological order, Internationalization of Tata Motors Limited, Strategic assets acquisition